The GH5 1, 4-β-mannanase from Bifidobacterium animalis subsp. lactis Bl-04 possesses a low-affinity mannan-binding module and highlights the diversity of mannanolytic enzymes. Issue 1 (December 2015) - Morrill, Johan; Kulcinskaja, Evelina; Sulewska, Anna; Lahtinen, Sampo; Stålbrand, Henrik; Svensson, Birte; Abou Hachem, Maher
Abstract Background β-Mannans are abundant and diverse plant structural and storage polysaccharides. Certain human gut microbiota members including health-promotingBifidobacterium spp. catabolize dietary mannans. Little insight is available on the enzymology of mannan deconstruction in the gut ecological niche. Here, we report the biochemical properties of the first family 5 subfamily 8 glycoside hydrolase (GH5_8) mannanase from the probiotic bacteriumBifidobacterium animalis subsp.lactis Bl-04 (Bl Man5_8). Results Bl Man5_8 possesses a novel low affinity carbohydrate binding module (CBM) specific for soluble mannan and displays the highest catalytic efficiency reported to date for a GH5 mannanase owing to a very highk cat (1828 ± 87 s-1 ) and a lowK m (1.58 ± 0.23 g · L-1 ) using locust bean galactomannan as substrate. The novel CBM ofBl Man5_8 mediates increased binding to soluble mannan based on affinity electrophoresis. Surface plasmon resonance analysis confirmed the binding of the CBM10 to manno-oligosaccharides, albeit with slightly lower affinity than the catalytic module of the enzyme. This is the first example of a low-affinity mannan-specific CBM, which forms a subfamily of CBM10 together with close homologs present only in mannanases. Members of this new subfamily lack an aromatic residue mediating binding to insoluble cellulose in canonical CBM10 members consistent with the observed low mannan affinity. Conclusion Bl Man5_8 is evolved for efficient deconstruction of soluble mannans, which is reflected by an exceptionally lowK m and the presence of an atypical low affinity CBM, which increases binding to specifically to soluble mannan while causing minimal decrease in catalytic efficiency as opposed to enzymes with canonical mannan binding modules. These features highlight fine tuning of catalytic and binding properties to support specialization towards a preferred substrate, which is likely to confer an advantage in the adaptation to competitive ecological niches.